Resource Extraction: The Enduring Legacy of Interference through the Papal Bulls (Fourth World Journal, 2025)
With aggressive tactics by companies with government support to extract resources and the continued effort to pass Bill C-262,2 an act which calls on Indigenous people and the Government of Canada to ensure the laws of Canada harmonize with the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP),it is necessary to delve deeper into what underlies the resource extractive industry and the emergence of this legislation.This article begins with a brief discussion of the UNDRIP and the refusal of Canada to participate in the World Conference on Indigenous Peoples. Delving deeper brings forward three particular papal bulls or proclamations that encouraged interference—the disruption of relationships—and gave expression to the Doctrine of Discovery and colonization. This interference continues today in the vivid example of the resource extractive industries. Because the papal bulls are the structural foundation for the Doctrine and colonization, reconciliation necessitates rescinding those bulls. Passing Bill C-262 re-establishes the relationship between Indigenous and non-Indigenous peoples; one characterized by respect, trust, equity and collaboration.